Perceived Threat of the Coronavirus and the Role of Trust in Safeguards: A Case Study in Slovakia - Kanovsky, Martin; Halamová, Júlia (Frontiers in Psychology, 2020)
In this exploratory research study we developed an instrument to investigate people’s confidence in safeguarding measures (Confidence in Safeguards Scale – CSS) and we adapted a instrument measuring perceived risk of coronavirus (Perceived Risk of Coronavirus Scale – PRCS), which was originally based on a perceived risk of HIV measure. We then explored the effect of public confidence in safeguarding measures designed to halt the spread of the coronavirus on perceived risk, controlling for related covariates. The sample consisted of N = 565 respondents; 119 were males (21.1 %) and 446 were females (78.9 %). Mean age was 35.42 (SD = 13.11), range 18–77 years. We used convenience sampling to gather the data at the end of March 2020 via social media in Slovakia. The CSS showed good reliability levels and a three-factor structure: Confidence in Institutions, Confidence in Personal and Family Behaviours, and Confidence in Others’ Behaviours. The PRCS showed good reliability levels and a two-factor structure: Fear of Contraction and Perceived Likelihood of Contraction. Participants with higher levels of Confidence in Others’ Behaviours perceived the spread of the coronavirus to be less threatening, both cognitively (less perceived likelihhod of contraction) and affectively (less fear of contraction). This finding could be used when designing public health policy and emergency communication. Enhancing confidence in others’ behaviours could encourage individual responsibility, social responsibility and solidarity through social bonds extending beyond the family. In future research we plan to replicate the data collection using the same instruments in different countries so the results are comparable across cultures and can be used to improve emergency communication.